Decision-making impairment in patients with multiple sclerosis: a case–control study. Issue 7 (29th July 2014) - Farez, Mauricio F; Crivelli, Lucía; Leiguarda, Ramón; Correale, Jorge
Abstract : Objectives: To assess decision-making under explicit risk conditions in relapsing–remitting multiple sclerosis patients and its relationship to decisions made under conditions of ambiguity. To assess cognitive functions related to decision-making performance in patients with multiple sclerosis (MS). Setting: MS center in Buenos Aires, Argentina. Participants: 27 patients with relapsing–remitting multiple sclerosis and 27 sex-matched, age-matched and education-matched healthy controls. Intervention: Neuropsychological assessment and decision-making evaluation using the Game of Dice Task and the Iowa Gambling Task. Outcomes: Game of Dice Task and the Iowa Gambling Task scores. Results: Patients with MS showed significantly poorer performance on the Game of Dice Task, choosing disadvantageous dice more often (p=0.019), as well as significantly lower overall scores in the Iowa Gambling Task (p=0.007). Block analysis showed that patients with MS and controls had scores that were comparable for blocks 1 and 2 (p=0.15 and p=0.24, respectively). Conversely, patients with MS scored poorly on blocks 4 (p=0.003) and 5 (p=0.023), the last two of the test, corresponding to decision-making under conditions of risk. Finally, the Game of Dice Task performance together with the last three blocks of the Iowa Gambling Task were correlated with visuospatial learning, processing speed and working memory but not with executive functioning. Conclusions: Patients with MS showed deficits in decision-making under risk conditions, which might be related to deficits in visuospatial learning, processing speed and working memory.